Investigation of the Time Behavior of the Second-Order Coherence Function of a Tunable Single-Photon Source - Ahmadian, Azadeh; Malekfar, Rasoul (Journal of Spectroscopy, 2021)
Single-photon sources are critical optical components in quantum communication, in particular, for security applications. One of the essential parameters that define these sources is the magnitude of the second-order coherence function, whose investigation reveals the state of the emitted photon. In this study, we indicate that the second-order coherence function varies over time when using two lasers and preparing coherent population trapping. The calculation is based on solving the master equation to find the density matrix corresponding to the emission dynamics and provide the second-order coherence function. The changes of the second-order coherence function can be estimated and the system behavior regarding photon emission can be predicted by solving the master equation based on the parameters obtained from the experimental results of a nitrogen vacancy (NV) in a diamond. Here we report, for the first time to the best of our knowledge, that the state of the emitted photons persists in the strong interaction of the aforementioned process. As using two lasers is a familiar method for controlling the single-photon source and the stability of the source is an essential point in a quantum network, this study can be considered to develop quantum network components such as memory and on-demand single-photon sources. Also, it suggests a method for tuning photon statistics while controlling the photon states.